Do emotional stimuli interfere with response inhibition? evidence from the antisaccade paradigm. Issue 8 (17th November 2021) - Hoffmann, Alexandra; Büsel, Christian; Ritter, Marcel; Sachse, Pierre
ABSTRACT: When it comes to measuring cognitive control and inhibition, the antisaccade paradigm is a popular task to apply. Usually, simple, perceptually and affectively neutral stimuli, e.g. white circles, are used. Recently, researchers also employed a version of the paradigm displaying emotional faces. Differences in cognitive processing due to stimulus size and emotional valence have not been investigated yet. Thus, in the present study, we applied both versions of the antisaccade paradigm in a healthy sample. In addition, we used scrambled faces to control for stimulus size and emotional valence. We hypothesised slower reaction times and higher error rates for emotional face stimuli compared to circular and scrambled ones as well as significant differences between individual emotions. In contrast to our hypotheses, results showed faster reaction times fewer errors for emotional faces compared to circular and scrambled stimuli. Furthermore, ANOVA models showed no meaningful differences between different emotions. Our study shows specific patterns in inhibitory control due to stimulus size and valence in an antisaccade eye-tracking task.